Keteladanan Tuhan Yesus Berdasarkan Filipi 2:1-11 Sebagai Landasan Bagi Hamba Tuhan - Parulian, Tamba; Emeliana, Emeliana (Basilius Eirene Press, 2022)
The Lord Jesus set His heart to fight so that He would not fall into sin, because if He fell into sin only once then the Lord Jesus was not worthy to atone for human sins. The Lord Jesus obeyed His Father more than obeyed the devil. As a servant of God in this uncertain era, even the Bible says these days are evil, it is important for God's servants to imitate the life attitude of the Lord Jesus who strives to be pleasing before His Father. The purpose of this study is to find the example of the Lord Jesus based on Philippians 2:1-11. The method used is qualitative by utilizing journals, books, and previous research. The results of this study are to put the thoughts and feelings contained in Christ Jesus, take the form of a servant, humble themselves and obey until death.